Invasion ratcheting in the zebra mussel (Dreissena polymorpha) and the ability of native and invaded ranges to predict its global distribution. (31st July 2013) - Gallardo, Belinda; zu Ermgassen, Philine S. E.; Aldridge, David C.
Abstract: Aim: In this study, we investigate changes in the environmental niche of an important pest species, the zebra mussel ( Dreissena polymorpha ), across its world‐wide distribution. The ability of models based on the native (Ponto‐Caspian) and invaded (Western European and North American) ranges to accurately model the potential distribution of zebra mussel elsewhere was also investigated. Location: Europe and North America. Methods: A comprehensive cross‐continental occurrence database of the zebra mussel was used to explore the species' native and invaded ranges using univariate and multivariate analyses. In addition, ecological niche models (ENMs, employingMaxEnt ) were used to investigate the ability of the native and invaded ranges to describe the species' distribution elsewhere. Results: We found the zebra mussel to occupy different, but partly overlapping, environmental niches in the native Ponto‐Caspian region and invaded European and North American regions. Accordingly, the ENMs calibrated with the native range accurately predicted regions of early colonization in Europe and North America, but not the subsequent expansion. ENMs calibrated with data from the European range failed to describe the invaded range in North America, and vice versa. Climate suitability curves further confirmed a progressive spatio‐temporal stretching of the climatic tolerance of the zebra mussel. Main conclusions: This study provides novel evidence of multiple episodes of niche expansion in a notorious invasive species, and supports the use of partial ranges to better understand the species' spatio‐temporal history of invasion. Separately, the native and invaded ranges provided important information regarding the species' environmental tolerance and the regions that are most suitable for first colonization, as well as identifying regions at risk in the case of a possible reintroduction. Collectively, the differences between the three ecological niche projections of the zebra mussel demonstrate that niche expansion of an invasive species within a new geographical region promotes the organism's further invasion in space and time, a process known as invasion ratcheting.